2011
DOI: 10.1002/ejoc.201100558
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dipolar Cycloaddition of Nitrile Imines with Cyclic α‐β‐Unsaturated Ketones: A Regiochemical Route to Ring‐Fused Pyrazoles

Abstract: Abstract1,3‐Dipolar cycloadditions of C‐carboxymethyl‐N‐arylnitrile imines with cyclic α,β‐unsaturated ketones of various sizes have been studied. After cycloaddition, oxidative aromatization gives the ring‐fused pyrazoles. Computational studies and the use of topological analyses of the Fukui functions allows a theoretical description of the local reactivity that is in agreement with the experimentally observed regiochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The Chemistry of fused pyrazolo- and thieno-pyrazole moieties has drawn great attention due to their pharmacological importance as reported earlier [29, 30, 31]. M. G. Prabhudeva et al, in 2018 reported the synthesis of bioactive thiophene-pyrazole conjugates and screened further for their antimicrobial and anti-oxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…The Chemistry of fused pyrazolo- and thieno-pyrazole moieties has drawn great attention due to their pharmacological importance as reported earlier [29, 30, 31]. M. G. Prabhudeva et al, in 2018 reported the synthesis of bioactive thiophene-pyrazole conjugates and screened further for their antimicrobial and anti-oxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, the chemistry of fused pyrazole derivatives has received great attention due to their pharmacological importance. 11,12 It has been found that pyranopyrazoles are an important class of biologically active heterocycles. They are reported to possess a multiplicity of pharmacological properties including anticancer, 13 antimicrobial, 14 anti-inflammatory, 15 insecticidal and molluscicidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Many literature reviews suggest that the pharmacophore hybrids may have enhanced efficacy, fewer drug–drug interactions, and less potential to induce drug resistance [ 26 ]. In light of the significance of pyrazoles and thiazoles, numerous studies have been conducted on the synthesis and biological evaluations of new hybrid pharmacophores containing pyrazole and thiazole moieties [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%